ANALYSIS OF THE INFLUENCE OF REGIONAL FINANCIAL INDEPENDENCE, PERCAPITA INCOME AND THE NUMBER OF POOR PEOPLE ON HUMAN DEVELOPMENT INDEX IN INDONESIA - Tiur Roida Simbolon (Universitas Negeri Medan, 2022)
The human development index is an important indicator to measure success in efforts to build human quality of life. Human development emphasizes the fulfillment of a life worthy of man. The government is making efforts to improve the quality of the population as a resource, both from aspects of education such as subsidies contained in the law, in terms of health and economic perspectives that can be seen from the income of the community. In this study, the authors analyzed how the influence of regional financial independence, percapita income and the number of poor people as an effort in the process of improving human development in each province in Indonesia. The research data was taken from 34 provinces in Indonesia with a period from 2014-2018 through the Central Statistics Agency. Through chow test and hausman test, this study used panel data analysis with Fixed Effect Model (FEM) approach. The results of partial or t-tests showed that regional financial independence had a significant effect on the human development index with a statistical t-value of 3,100864 and a probability of α < 0.05, Per capita GDP data has a significant effect on the human development index with a statistical t-value of 5,131457 and a probability of α < 0.05, and the number of poor people has a significant effect on the human development index with a statistical t-value of -16,10742 and a probability of α < 0.05. Simultaneous test results or F-test showed a statistical F-value of 74,08607 with a probability of α < 0.05 which means that together independent variables have a significant effect on dependent variables. Through the R² test results obtained a value of 0.952502 means variables of regional financial independence, percapita income and the number of poor people are able to explain the effect on the human development index in each province in Indonesia by 95 percent ____________________________________________________________Keywords: Regional Financial Independence (KKD), Perkapita Income (GDPperkapita), Number of Poor People (JPM), Human Development Index (HDI), Fixed Effect Model (FEM)